An alternative definition for the k-Riemann liouville fractional derivative - Dorrego, Gustavo Abel (Hikari Ltd, 2015)
The aim of this paper is to introduce an alternative de nition for the k-Riemann-Liouville fractional derivative given in [6] and whose advantage is that it is the left inverse of the corresponding of k-Riemann-Liouville fractional integral operator introduced by [5]. Its basic properties are discussed, their Laplace transform, the derivative of the potential function and the derivative of the Mittag-Le er k-function introduced in is calculated.
Keywords: K-fractional calculus; K-riemann-liouville fractional integral; Matemáticas